Ayurvedic mediated green synthesis of gold and silver nanoparticles from marine microalgae Isochrysis sp. - Tevan, Ramanathan; Kuppusamy, Palaniselvam; Govindan, Natanamurugaraj; Abdul Rahim, Mohd Hasbi; Ichwan, Solachuddin J. A.; Maniam, Gaanty Pragas (Science Publishing Corporation (UEA), 2018)
Ayurveda is an Indian traditional medicinal system. Yet Ayurveda remains in living tradition. There has been an increased global interest in traditional medicine systems. Asavas is a novel yet less exploited hydro extraction method in Ayurveda. As green synthesis of metal nanoparticles is widely under exploration in the current research world, synthesis of gold and silver nanoparticles by employing the Ayurveda method using marine microalgae is tested in this research. The characterization of metal nanoparticles was confirmed by UV- Visible Spectroscopy, field emission scanning electron microscopy (FESEM), and Fourier transform infrared spectroscopy (FT-IR). Through the Arishtas method, gold and silver nanoparticles were successfully isolated from Isochrysis sp. The synthesized nanoparticles exhibit excellent antioxidant and antimicrobial activities.